2010
DOI: 10.1088/1748-9326/5/3/034013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Copenhagen Accord pledges and its global climatic impacts—a snapshot of dissonant ambitions

Abstract: This analysis of the Copenhagen Accord evaluates emission reduction pledges by individual countries against the Accord's climate-related objectives. Probabilistic estimates of the climatic consequences for a set of resulting multi-gas scenarios over the 21st century are calculated with a reduced complexity climate model, yielding global temperature increase and atmospheric CO 2 and CO 2 -equivalent concentrations. Provisions for banked surplus emission allowances and credits from land use, land-use change and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
1
29
1
Order By: Relevance
“…Their results cannot be reconciled with those presented here based on the Bern2D intermediate complexity climate-carbon cycle model, or indeed with any of the zero emission-commitment or temperaturestabilization scenarios calculated by a climate model that resolves the relevant time scales and reservoirs of the energy balance and carbon cycle (Caldeira et al 2003;Hare and Meinshausen 2006;Weaver et al 2007;Matthews and Caldeira 2008;Plattner et al 2008;Allen et al 2009;Matthews et al 2009;Meinshausen et al 2009;Solomon et al 2009;Zickfeld et al 2009;Frö licher and Joos 2010;Rogelj et al 2010;Solomon et al 2010;Gillett et al 2011).…”
Section: Discussioncontrasting
confidence: 60%
“…Their results cannot be reconciled with those presented here based on the Bern2D intermediate complexity climate-carbon cycle model, or indeed with any of the zero emission-commitment or temperaturestabilization scenarios calculated by a climate model that resolves the relevant time scales and reservoirs of the energy balance and carbon cycle (Caldeira et al 2003;Hare and Meinshausen 2006;Weaver et al 2007;Matthews and Caldeira 2008;Plattner et al 2008;Allen et al 2009;Matthews et al 2009;Meinshausen et al 2009;Solomon et al 2009;Zickfeld et al 2009;Frö licher and Joos 2010;Rogelj et al 2010;Solomon et al 2010;Gillett et al 2011).…”
Section: Discussioncontrasting
confidence: 60%
“…1 Illustration of the effect of the current emissions reduction proposals under the Copenhagen Accord. Besides the pathways representing a business-as-usual scenario (BAU very close to SRES A1B, Nakicenovic et al 2000) and the estimated emissions based on the Copenhagen Accord proposals (Rogelj et al 2010a;Rogelj et al 2010b), four low-emission pathways are shown. The black dashed line indicates the expected temperature projections if all global emissions (greenhouse gases and aerosols) would become zero in 2016.…”
Section: Discussionmentioning
confidence: 98%
“…[2] To date, mitigation efforts through international political agreements have been slow to reduce greenhouse gas emissions [Rogelj et al, 2010] and stabilizing atmospheric CO 2 will likely require contributions from multiple approaches [e.g., Pacala and Socolow 2004;Royal Society, 2009] [Royal Society, 2009] but both depend on identifying suitable long-term reservoirs. Most attention to date has focused on the potential of geologic storage [Dooley et al, 2006], where CO 2 is injected into depleted oil and gas fields or deep saline aquifers.…”
Section: Introductionmentioning
confidence: 99%